2009
DOI: 10.1212/wnl.0b013e3181a2e90a
|View full text |Cite
|
Sign up to set email alerts
|

Changes in MRS neuronal markers and T cell phenotypes observed during early HIV infection

Abstract: Objective: To determine if changes in brain metabolites are observed during early HIV infection and correlate these changes with immunologic alterations.Methods: Eight subjects with early HIV infection, 9 HIV-seronegative controls, and 10 chronically HIV-infected subjects without neurologic impairment underwent 1 H magnetic resonance spectroscopy. Subjects with early stage infection were identified near the time of HIV seroconversion and imaged within 60 days of an evolving Western blot, while still having det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
76
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 38 publications
10
76
0
Order By: Relevance
“…Additionally, Cho and Cho/Cr levels increased initially in all three ROIs at peak viremia, indicating macrophage infiltration, but then decreased below baseline by the fourth week. Another 2009 study [75] of patients with early HIV infection confirmed some of the findings of the Westmorland study [62], including a sharp decline of NAA in the frontal cortex that was significantly correlated with expansion of CD8+ T cells. Thus, neuronal injury occurs in the frontal cortex as early as 2 weeks following the initial infection with HIV, suggesting that an increase in NAA may serve as a surrogate marker for therapy effectiveness in early stage treatment regimens.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 55%
See 1 more Smart Citation
“…Additionally, Cho and Cho/Cr levels increased initially in all three ROIs at peak viremia, indicating macrophage infiltration, but then decreased below baseline by the fourth week. Another 2009 study [75] of patients with early HIV infection confirmed some of the findings of the Westmorland study [62], including a sharp decline of NAA in the frontal cortex that was significantly correlated with expansion of CD8+ T cells. Thus, neuronal injury occurs in the frontal cortex as early as 2 weeks following the initial infection with HIV, suggesting that an increase in NAA may serve as a surrogate marker for therapy effectiveness in early stage treatment regimens.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 55%
“…For example, Lentz et al [75] recently used factor analysis to analyze the metabolic variance in seven different regions of the brain as well as immunologic measures and cognitive dysfunction. As a result, several statistically significant surrogate markers emerged for prognosis and for therapeutic monitoring of patients with HIV infection.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…Proton ( 1 H) magnetic resonance spectroscopy (MRS) provides measures of specific metabolites that reflect different pathological processes. Numerous MRS studies of HIV have demonstrated abnormalities of the cerebral metabolites N-acetylaspartate (NAA), myo-inositol (MI), choline-containing compounds (Cho), and glutamate/glutamine (Glx) Schifitto et al, 2009a;Schweinsburg et al, 2005;Paul et al, 2007;Lentz et al, 2009). Decreased NAA is known to reflect neuronal injury or loss, whereas increased Cho and MI have been linked to proinflammatory processes, and a breakdown of cell membranes (Ross and Bluml, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, asymptomatic HIV infection, a group which is often neglected, is hardly taken into consideration in scientific research. 6,9,14,19 In this study, asymptomatic HIV-positive adolescent orphans, who were born with HIV owing to mother-to-child transmission, were scanned using DWI with multi-b-value. The immune system of infants was immature and immune system function was poor.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are in the asymptomatic stage, their nervous system may have been attacked by HIV. Some scholars 6,14,[19][20][21] indicated that central nervous system has been involved in the course of HIV infection in the early stage of the disease. We hope to identify the damaged parts of the nervous system and make a prediction of opportunistic infections by analyzing apparent diffusion coefficient (ADC), distribution diffusion coefficient (DDC) and heterogeneity index (a) values.…”
Section: Introductionmentioning
confidence: 99%